Effectiveness of telemedicine for the prevention of mother-to-child transmission of HIV in low-income and middle-income countries: a systematic review and meta-analysis - Dantong Li; Shang Ma; Binfei Dang; Huifeng Shi; Yuan Wei; Xiaoli Wang (International Journal of Infectious Diseases, 2024)
Objectives: We aimed to estimate the effectiveness of telemedicine for the prevention of mother-to-child transmission (PMTCT) program of HIV in low- and middle-income countries (LMICs). Methods: We did a systematic literature search of 15 databases for articles published from database inception to October 26, 2022, and performed meta-analyses to estimate the pooled risk ratio of intervention effect (RR) and its 95% confidence interval (CI). We used subgroup analyses and meta-regressions to explore variation in the RRs. Funnel plots and Egger regression tests were also performed to assess publication bias. Results: Seventeen studies were included in the systematic review, with a total sample size of 9118 participants. We found that telemedicine was beneficial for early infant diagnosis (EID) in the sixth week (RR 1.04 [95% CI 1.00-1.09]), exclusive breastfeeding (RR 1.12 [95% CI 1.01-1.24]) and PMTCT retention (RR 1.34 [95% CI 1.16-1.55]). However, we did not find a significant effect of telemedicine on infant prophylaxis, HIV transmission, and ART adherence. Besides, the heterogeneity of ART adherence was associated with enrollment time, while retention was related to ART initiation. Conclusions: Our meta-analysis demonstrated the benefits of telemedicine in improving PMTCT, especially for EID, exclusive breastfeeding, and PMTCT retention.